1997
DOI: 10.1088/0953-8984/9/47/014
|View full text |Cite
|
Sign up to set email alerts
|

Anderson impurity in pseudo-gap Fermi systems

Abstract: We use the numerical renormalization group method to study an Anderson impurity in a conduction band with the density of states varying as ρ(ω) ∝ |ω| r with r > 0. We find two different fixed points: a local-moment fixed point with the impurity effectively decoupled from the band and a strong-coupling fixed point with a partially screened impurity spin. The specific heat and the spin-susceptibility show powerlaw behaviour with different exponents in strong-coupling and localmoment regime. We also calculate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
353
2
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(382 citation statements)
references
References 19 publications
26
353
2
1
Order By: Relevance
“…The authors of Ref. 10 interpret these results, and certain noninteger exponents describing their numerical data for the impurity spectral function, as evidence for non-Fermiliquid behavior. We demonstrate, however, that the fixed-point properties are precisely those expected for a noninteracting gapless system.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The authors of Ref. 10 interpret these results, and certain noninteger exponents describing their numerical data for the impurity spectral function, as evidence for non-Fermiliquid behavior. We demonstrate, however, that the fixed-point properties are precisely those expected for a noninteracting gapless system.…”
Section: Introductionmentioning
confidence: 89%
“…Bulla et al 10 have recently presented an ansatz for t n when the scattering rate has the pure power-law form given in Eq. (1.3).…”
Section: Discretization Of the Conduction Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated magnetic adatoms placed on monolayer graphene sheets (MLG) have been studied experimentally as well as theoretically [87,88], and the properties of the Kondo ground state have been a subject of controversy [84,[89][90][91][92][93][94][95]. The Kondo effect due to magnetic adatoms such as cobalt, present different behaviors depending on the position of the impurities in graphene sublattices.…”
Section: Introductionmentioning
confidence: 99%
“…it has a pseudo-gap at the Fermi level which scales linearly. Studies of impurities in pseudo-gap systems [89,90] have shown there is a critical coupling, J c , below which the Kondo effect does not take place [95]. This opens the door for an effective RKKY state to emerge.…”
Section: Introductionmentioning
confidence: 99%